Online Grocery Shopping: A Consumer Behaviour Perspective - Govindasamy, Devananthan (2008)
In this study , we will see what are the common factors that empirically influence the buyingbehavior of customers through online click of a mouse as opposed throughthe traditional brick-mortar way.